2013
DOI: 10.1089/jop.2012.0129
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Toxicity of Intravitreal Trastuzumab in a Rabbit Model: Preliminary Results of an Experimental Study

Abstract: Intravitreal trastuzumab seems to be toxic to the retina in albino rabbits even at a concentration of 5 mg/mL. Further studies are needed to evaluate the safety of intravitreal trastuzumab in models of choroidal neovascularization, as well as to obtain experience concerning the intravitreal toxicity of trastuzumab in primates too and not only in rabbits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Preclinical studies showed that trastuzumab, a full-length IgG antibody, was not capable of crossing the retinal limiting inner membrane of the retina, thus, smaller molecules were proposed for treating PDR and AMD [109,110].…”
Section: Ocular Immunotherapy In Pathological Angiogenesismentioning
confidence: 99%
“…Preclinical studies showed that trastuzumab, a full-length IgG antibody, was not capable of crossing the retinal limiting inner membrane of the retina, thus, smaller molecules were proposed for treating PDR and AMD [109,110].…”
Section: Ocular Immunotherapy In Pathological Angiogenesismentioning
confidence: 99%